Self-Targeting of Carbon Dots into the Cell Nucleus: Diverse Mechanisms of Toxicity in NIH/3T3 and L929 Cells - Havrdová, Markéta; Urbančič, Iztok; Bartoň Tománková, Kateřina; Malina, Lukáš; Štrancar, Janez; Bourlinos, Athanasios B (International journal of molecular sciences, 2021)
It is important to understand the nanomaterials intracellular trafficking and distribution and investigate their targeting into the nuclear area in the living cells. In our previous study, we firstly observed penetration of nonmodified positively charged carbon dots decorated with quaternary ammonium groups (QCDs) into the nucleus of mouse NIH/3T3 fibroblasts. Thus, in this work, we focused on deeper study of QCDs distribution inside two healthy mouse NIH/3T3 and L929 cell lines by fluorescence microspectroscopy and performed a comprehensive cytotoxic and DNA damage measurements. Real-time penetration of QCDs across the plasma cell membrane was recorded, concentration dependent uptake was determined and endocytic pathways were characterized. We found out that the QCDs concentration of 200 µg/mL is close to saturation and subsequently, NIH/3T3 had a different cell cycle profile, however, no significant changes in viability (not even in the case with QCDs in the nuclei) and DNA damage. In the case of L929, the presence of QCDs in the nucleus evoked a cellular death. Intranuclear environment of NIH/3T3 cells affected fluorescent properties of QCDs and evoked fluorescence blue shifts. Studying the intracellular interactions with CDs is essential for development of future applications such as DNA sensing, because CDs as DNA probes have not yet been developed.
Keywords: Animals; NIH/3T3; Microscopy, Fluorescence; cytotoxicity; nucleolus; Fibroblasts; Cell Cycle; genotoxicity; Cell Nucleus; Mice; fibroblasty; carbon dots; fluorescenční mikroskopie; myši; fluorescence microspectroscopy; buňky NIH 3T3; NIH 3T3 Cells; buněčný cyklus; buněčné jádro; L929; fibroblasts; cnucleus; Quantum Dots; kvantové tečky; Cell Survival; zvířata; viabilita buněk; buněčná membrána; Carbon; uhlík; Cell Membrane